ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DAN HARGA JUAL IKAN BANDENG MENGGUNAKAN FULL COSTIGN (STUDI PADA PETANI IKAN BANDENG DESA MADUMULYOREJO GRESIK ) - Khamdan Suriyok (Institut Teknologi dan Bisnis Yadika, 2021)
Based on the phenomena or problems faced by Vaname shrimp entrepreneurs, it is in determining the cost of production and determining the selling price of products that are not appropriate, so they often fail to compete with other Vaname shrimp entrepreneurs. The purpose of this study was to analyze the comparison between the calculation of the cost of production and the company's cost of goods sold using the Full Costing approach. The method in this study is a descriptive qualitative method by means of direct interviews with informants The results of the study can be concluded that the cost of production for Vaname shrimp entrepreneurs has not shown the cost of production in accordance with the collection of production costs. There is a difference in determining the cost of goods according to the company of Rp. 17,309.48 and according to the author based on the theory of Rp. 19,848.57. This has not been used as the basis for determining the selling price because the determination of the selling price is not in accordance with the theory that the company does not take into account the percentage of expected profit but is only based on market prices.